escreva o polinomio que representa cada produto a) (3x-5)×(5x+2)=

b) (x+y)×(x²-5xy+y³) =


c) (0,6x+5)×(0,1-x)=​


Resposta :

Explicação passo-a-passo:

a) (3x - 5) × (5x + 2)=

[tex]15 {x}^{2} + 6x - 25x - 10 = \\ 15 {x}^{2} - 19x - 10[/tex]

b) (x + y) × (x² - 5xy + y³) =

[tex] {x}^{3} - 5 {x}^{2} y + x {y}^{3} + {x}^{2} y - 5x {y}^{2} + {y}^{4} = \\ {x}^{3} - 4 {x}^{2} y - 5x {y}^{2} + x {y}^{3} + {y}^{4} [/tex]

c) (0,6x + 5) × (0,1 - x) =

[tex]0.06x - 0.6 {x}^{2} + 0.5 - 5x = \\ - 0.6 {x}^{2} - 4.94x + 0.5[/tex]